1996
DOI: 10.1177/096120339600500305
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of five health status instruments in patients with systemic lupus erythematosus (SLE)

Abstract: The aim of the present investigation was to assess and compare health status instruments in SLE. One hundred and twenty-five patients completed five health status instruments: the Health Assessment Questionnaire (HAQ), Functional Ability Index, the Fatigue Severity Scale (FSS), the Disability Days Measure (DDM), the Centre for Epidemiological Studies-Depression Scale (CES-D), and the Medical Outcomes Study (MOS) Short Form Health Survey during their Clinic visit. Disease activity was measured using the SLE Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 13 publications
3
57
1
3
Order By: Relevance
“…We have confirmed this in the current study (Figure 1). Many studies have found no correlation between the SF-36 and disease activity (12,15,16). Others have found a relationship between the SF-36 and disease activity using the Systemic Lupus Activity Measure, or British Isles Lupus Assessment Group (18,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have confirmed this in the current study (Figure 1). Many studies have found no correlation between the SF-36 and disease activity (12,15,16). Others have found a relationship between the SF-36 and disease activity using the Systemic Lupus Activity Measure, or British Isles Lupus Assessment Group (18,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistent results have been reported regarding the influence of disease activity and damage on quality of life. Some studies have demonstrated a lack of correlation among these outcomes while others have shown disease variables to be strong predictors of quality of life (12)(13)(14)(15)(16)(17)(18). A recent review of quality of life in SLE concluded that there was no correlation with disease activity or damage (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended as the instrument to measure quality of life in patients with SLE by the Systemic Lupus International Collaborating Clinics Group (SLICC) [1]. The SF-36 is a valid and reliable tool that identifies the physical, psychological, and social influence of the disease on patients with SLE [4,5]. However, longitudinal studies that assessed HRQoL of patients with SLE have shown that SF-36 is not sensitive to change when administered biannually or yearly [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Das schränkt eine Bewertung über serologische Parameter wesentlich ein. Und schließlich gibt es mit der Erkrankung assoziierte Symptome, wie die häufige Abgeschlagenheit (Fatigue), die offenbar oft nicht mit der Krankheitsaktivität gekoppelt ist [18,27,32,46] und deren Genese nicht ausreichend erforscht erscheint [33]. …”
unclassified